The population dynamics of haemoglobins A, A2, F and S in the context of the haemoglobinopathies HbS and α+thalassaemia in Kenyan infants - Macharia, A; Uyoga, S; Ndila, C; Nyutu, G; Makale, J; Tendwa, M; Nyatichi, E; Ojal, J; Atkinson, S; Williams, T (Ferrata Storti Foundation, 2018)
Few studies have described the dynamics of haemoglobin production in African populations with a high prevalence of haemoglobinopathies. We have used the BioRad Variant ClassicTM HPLC method to document the production patterns of the common haemoglobin variants HbA, HbA2, HbF and HbS, stratified by a+thalassaemia genotype, among 15,301 infants recruited to a study on the Coast of Kenya. Notably, we confirm that HbA2 measurements determined using this instrument are unreliable in HbAS and HbSS subjects. Further, we showed that HbA2 exceeded 4.0%, a level consistent with the presence of a-thalassaemia, in 0.8% of infants of HbAA phenotype who participated in our study. a-thalassaemia, has not been widely reported in the East Africa region and, as such, this finding merits further study.